2019
DOI: 10.1002/jclp.22825
|View full text |Cite
|
Sign up to set email alerts
|

Intrapersonal and interpersonal facilitators of forgiveness following spousal infidelity: A stress and coping perspective

Abstract: Objective Forgiveness includes processes that involve a decision to stop bitterness and thoughts of revenge (i.e., decisional forgiveness), which further motivates the forgiver towards the restoration of positive emotions (i.e., emotional forgiveness). Using stress and coping framework, this study investigated intrapersonal and interpersonal facilitators of decisional and emotional forgiveness in a Chinese marital context. Method Participants were 154 respondents who had experienced or were experiencing spousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
(120 reference statements)
1
10
1
2
Order By: Relevance
“…A second limitation is the use of the recall method. First, the accuracy of the recall may be doubtful, as this kind of retroactive reporting could easily be colored by selective memory or current mood or recovery stages ( Chi et al, 2019 ). For example, when participants recalled a hurtful incident from the past, they may have recalled events that they perceived as particularly severe, which could have affected the longevity of the effects found in our study (although identical findings were found when including and excluding perceived severity as a control variable – Appendix B ).…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is the use of the recall method. First, the accuracy of the recall may be doubtful, as this kind of retroactive reporting could easily be colored by selective memory or current mood or recovery stages ( Chi et al, 2019 ). For example, when participants recalled a hurtful incident from the past, they may have recalled events that they perceived as particularly severe, which could have affected the longevity of the effects found in our study (although identical findings were found when including and excluding perceived severity as a control variable – Appendix B ).…”
Section: Discussionmentioning
confidence: 99%
“…Holding unforgiveness and dwelling on injury escalates stress and might lead to anxiety, anger, avoidance and, consequently, depression ( Worthington and Wade, 1999 ). Forgiveness provides for transformation of negative feelings, thoughts and behaviors to neutral or positive ones, and it reduces stress ( Chi et al., 2019 ; Worthington and Scherer, 2004 ). Empirical research on stress and coping and their correlates, revealed strong relationships with forgiveness ( Crandall et al., 2019 ; Gall and Bilodeau, 2021 ; Ochu et al., 2018 ) which are differentiated by gender, age and culture.…”
Section: Introductionmentioning
confidence: 99%
“…Marital infidelity is a relationship transgression that could be sexual infidelity, emotional infidelity or a combination of sexual and emotional infidelity (Chi et al 2019). Some Christian couple divorce because they suspect their husband is seeing another woman or their wife is seeing another man.…”
Section: Infidelitymentioning
confidence: 99%